An efficient and general route to reduced polypropionates via Zr-catalyzed asymmetric C—C bond formation - Negishi, Ei-ichi (National Academy of Sciences, 2004)
An efficient and general method for the synthesis of reduced polypropionates has been developed through the application of asymmetric carboalumination of alkenes catalyzed by dichlorobis(1-neomenthylindenyl)zirconium [(NMI)(2)ZrCl(2)]. In this investigation, attention has been focused on those reduced polypropionates that are α-monoheterofunctional and either ω-ethyl or ω-n-propyl. The reaction of 3-buten-1-ol with triethylaluminum (Et(3)Al) or tripropylaluminum ((n)Pr(3)Al) in the presence of (NMI)(2)ZrCl(2) and isobutylaluminoxane gave, after protonolysis, (R)-3-methyl-1-pentanol as well as (R)- and (S)-3-methyl-1-hexanols in 88–92% yield in 90–92% enantiomeric excess in one step. These 3-monomethyl-1-alkanols were then converted to two stereoisomers each of 2,4-dimethyl-1-hexanols and 2,4-dimethyl-1-heptanols via methylalumination catalyzed by (NMI)(2)ZrCl(2) and methylaluminoxane followed by oxidation with O(2). The four-step (or three-isolation-step) protocol provided syn-2,4-dimethyl-1-alkanols of ≥98% stereoisomeric purity in ≈50% overall yields, whereas (2S,4R)-2,4-dimethyl-1-hexanol of comparable purity was obtained in 40% overall yield. Commercial availability of (S)-2-methyl-1-butanol as a relatively inexpensive material suggested its use in the synthesis of (2S,4S)- and (2R,4S)-2,4-dimethyl-1-hexanols via a three-step protocol consisting of (i) iodination, (ii) zincation followed by Pd-catalyzed vinylation, and (iii) Zr-catalyzed methylalumination followed by oxidation with O(2). This three-step protocol is iterative and applicable to the synthesis of reduced polypropionates containing three or more branching methyl groups, rendering this method for the synthesis of reduced polypropionates generally applicable. Its synthetic utility has been demonstrated by preparing the side chain of zaragozic acid A and the C11–C20 fragment of antibiotics TMC-151 A–F.